Penerapan metode Sorogan dalam upaya meningkatkan kemampuan membaca Al-Qur’an di Madrasah Tsanawiyah - Wijaya, Arya Suta; Gustiawati, Syarifah; Basri, Samsul (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
The ability to read the Qur'an among students at MTs Ulin Nuha Al-Islamic Center Bogor remains relatively low, particularly in terms of fluency, accurate pronunciation (makhraj), and the application of tajwid rules. This study aims to improve the Qur'an reading skills of Grade VIII students through the implementation of the sorogan method. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. The subjects consisted of 16 eighth-grade students. Instruments used in the research included observation sheets, interviews, and Qur'an reading tests. The results show a significant improvement in students’ reading ability following the implementation of the sorogan method. In the pre-cycle stage, only 12.5% of students reached the minimum competence criteria (MCC) in Qur'an reading. After implementing the sorogan method, student achievement increased to 50% in the first cycle and reached 87.5% in the second cycle. The average score also rose from 53.5 to 89. These findings indicate that the sorogan method is effective in improving students' ability to read the Qur’an through individualized, intensive, and targeted instruction. Abstrak Kemampuan membaca Al-Qur’an siswa MTs Ulin Nuha Al-Islamic Center Bogor masih tergolong rendah, terutama dalam aspek kefasihan, ketepatan makhraj, dan penerapan hukum tajwid. Penelitian ini bertujuan untuk meningkatkan kemampuan baca Al-Qur’an siswa kelas VIII melalui penerapan metode sorogan. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus. Subjek penelitian terdiri dari 16 siswa kelas VIII. Instrumen yang digunakan mencakup lembar observasi, wawancara, dan tes membaca Al-Qur’an. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam kemampuan membaca siswa setelah penerapan metode sorogan. Pada tahap pra-siklus hanya 12,5% siswa yang mencapai ketuntasan kemampuan membaca Al-Qur’an, setelah penerapan metode sorogan ketuntasan kemampuan membaca Al-Qur’an siswa meningkat menjadi 50% pada siklus I dan mencapai 87,5% pada siklus II. Rata-rata nilai siswa juga meningkat dari 53,5 ke 89. Simpulan dari penelitian ini membuktikan bahwa metode sorogan efektif dalam meningkatkan kemampuan membaca Al-Qur’an secara individual, intensif, dan terarah.